PENGARUH KUALITAS SUPERVISI AKADEMIK PENGAWAS SEKOLAH TERHADAP KINERJA GURU SAINS SMA NEGERI DI KOTA BAUBAU - Ratlin, Ratlin (PEP Educational Assessment, 2017)
Objective husband is to review to assess: (i) PERCEPTION OF SERVICE QUALITY science teachers regarding academic supervision supervisor high schools in the City Baubau ON dimensional Lesson Planning; (ii) PERCEPTION OF SERVICE QUALITY science teachers regarding academic supervision supervisor high schools in the City Baubau ON Learning Implementation dimension; And (iii) PERCEPTION OF SERVICE QUALITY science teachers regarding academic supervision supervisor high schools in the City Baubau ON husband pembelajaran.Penelitian Evaluation dimension is research-quantitative description using Survey Method TYPE WITH ex post facto. Population Research is a science teacher (teacher that administer eye Lessons of physics, chemistry, biology and) TO SMA in Baubau City. The study sample comprised 59 teachers orangutan differences Science The LEAD WITH ENGINEERING purposive random sampling. Research Data WITH TIN through the instruments in the reliability rate differences 75% based on the findings Gregory validity of the content. Research data were analyzed using analysis deskriptif.Hasil WITH Research shows that: (i) PERCEPTION OF SERVICE QUALITY science teachers regarding academic supervision supervisor high schools in the City Baubau It is categorized Good; (ii) the boarding costs of SMA science teacher at the City Baubau is ON Category Very Good; And (iii) ADA positively influence academic supervision QUALITY WITH A school superintendent boarding costs of SMA science teacher at the City Baubau